Adapting reading tasks in the textbook English 12 to improve 12th form students’ reading achievement = Điều chỉnh các nhiệm vụ đọc hiểu trong sách giáo khoa tiếng anh 12 nhằm nâng cao khả năng đọc hiểu của học sinh . M.A Thesis Linguistic: 60 14 10 - Vũ, Thị Thanh Huyền, 1985- (University of Languages and International Studies, 2017)
M.A. Thesis English Teaching Methodology -- University of Languages and International Studies. Vietnam National University, Hanoi, 2013